Analisis Risiko Produksi Stroberi pada UD Agro Mandiri di Desa Pancasari Kecamatan Sukasada Kabupaten Buleleng - GUSTI MADE OFFAYANA,; I WAYAN WIDYANTARA; I GUSTI AYU AGUNG LIES ANGGRENI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
ABSTRACT The Risk Analysis on Strawberries Production of UD Agro Mandiri at the Pancasari Village Sukasada Sub-district of the Buleleng Regency UD Agro Mandiri is one of the agribusiness companies, as well as agro-tourism located in the Village of Pancasari, Sub-district of Sukasada, the Buleleng Regency which produces strawberries in its agribusiness. The problem faced is the fluctuation of the production of strawberries, so that indicates the risks faced in producing strawberries, where the risk has caused decline in revenue to the company. The study aims to identify the sources of risk, to analyze the extent of the risk, and to find out the ways of tackling the risk of strawberry production specialization. The research method used qualitative and quantitative analysis. The result showed the sources of risk that affect the production of strawberries at UD Agro Mandiri namely: the weather conditions, pests and diseases, workers, visitors, and the quality of the seeds with relatively bigger level of risk, when it is seen from the standard deviation of 3,411 kg/year and the coefficient variation of 3.3. The risk management done by the company previously, has not been able to minimize the risk of strawberry production. It takes some ways in facing the risk of strawberry production, namely, building a greenhouse with hydroponic systems, making the SOP, adding the company's facilities, undertaking contract of production, developing vertical diversification, and making partnerships in the procurement of strawberry seeds. The company needs to implement the ways of handling as proposed, so that it can curb the risk into smaller level when producing strawberries. It also needs further research on the analysis of portfolio risk. Keyword : strawberry, production risks, specialization